Spatio‐temporal variation in ocean current‐driven hatchling dispersion: Implications for the world's largest leatherback sea turtle nesting region. Issue 6 (21st March 2017) - Scott, Rebecca; Biastoch, Arne; Agamboue, Pierre D.; Bayer, Till; Boussamba, Francois L.; Formia, Angela; Godley, Brendan J.; Mabert, Brice D. K.; Manfoumbi, Jean C.; Schwarzkopf, Franziska U.; Sounguet, Guy‐Philippe; Wagner, Patrick; et al.
Abstract: Aim: The lives of juvenile leatherback turtles are amongst the most enigmatic of all marine mega‐vertebrates. For these cryptic organisms, ocean models provide important insights into their dispersion from natal sites. Here, corroborated by fisheries bycatch data, we simulate spatio‐temporal variation in hatchling dispersion patterns over five decades from the World's largest leatherback turtle nesting region. Location: Equatorial Central West Africa (3.5°N to −6°S) spanning the Gulf of Guinea in the North, Gabon and the Republic/Democratic Republic of the Congo in the South. Results: Due to dynamic oceanic conditions at these equatorial latitudes, dispersion scenarios differed significantly: (1) along the north to south gradient of the study region, (2) seasonally and (3) between years. From rookeries to the north of the equator, simulated hatchling retention rates within the Gulf of Guinea were very high (>99%) after 6 months of drift, whilst south of the equator, retention rates were as low as c . 6% with the majority of simulated hatchlings dispersing west into the South Atlantic Ocean with the South Equatorial Current. Seasonal dispersion variability was driven by wind changes arising from the yearly north/southward migration of the intertropical convergence zone resulting in the increasing westerly dispersion of hatchlings throughout the hatching season. Annual variability in wind stress drove a long‐term trend for decreased retention within the Gulf of Guinea and increased westerly dispersion into habitats in the South Atlantic Ocean. Main conclusions: Shifts in dispersion habitats arising from spatio‐temporal oceanic variability expose hatchlings to different environments and threats that will influence important life history attributes such as juvenile growth/survival rates; anticipated to impact the population dynamics and size/age structure of populations into adulthood. The impacts of local and dynamic oceanic conditions thus require careful considerations, such as subregional management, when managing marine populations of conservation concern.